Nucleic Acid-Based Therapeutics for Pulmonary Diseases - Chen, Jing (AAPS PharmSciTech, 2018)
Nucleic acid-based therapeutics present huge potential in the treatment of pulmonary diseases ranging from lung cancer to asthma and chronic pulmonary diseases, which are often fatal and widely prevalent. The susceptibility of nucleic acids to degradation and the complex structure of lungs retard the effective pulmonary delivery of nucleic acid drug. To overcome these barriers, different strategies have been exploited to increase the delivery efficiency using chemically synthesized nucleic acids, vector encapsulation, proper formulation, and administration route. However, several limitations regarding off-target effects and immune stimulation of nucleic acid drugs hamper their translation into the clinical practice. Therefore, their successful clinical application will ultimately rely on well-developed carriers and methods to ensure safety and efficacy. In this review, we provide a comprehensive overview of the nucleic acid application for pulmonary diseases, covering action mechanism of the nucleic acid drugs, the novel delivery systems, and the current formulation for the administration to lungs. The latest advances of nucleic acid drugs under clinical evaluation to treat pulmonary disorders will also be detailed.